Analyzing Asynchronous Online Discussions in Solid-State Physics: Interaction Patterns and Cognitive Presence Among Distance Learners - Widiasih; Arisona; Dwikoranto; Rahmawati; Ismail (Universitas Muhammadiyah Makassar, 2025)
The increasing adoption of online learning in higher education has placed asynchronous discussion forums at the center of teaching and learning, particularly in open and distance learning contexts where student engagement and collaborative inquiry are crucial. In physics education, however, fostering deep conceptual understanding through asynchronous communication remains challenging, as participation often tends to be surface-level and tutor-centered. This study aimed to analyze participation patterns, levels of cognitive presence, and their relationship to student performance in a Solid-State Physics course at Universitas Terbuka, Indonesia. Employing a descriptive case study design, the research collected data from learning management system logs, forum transcripts, tutor feedback, and assignment scores. Cognitive presence was coded using the Community of Inquiry framework, intercoder reliability was established with Cohen’s kappa (κ = 0.88), and interaction structures were visualized using social network analysis. The results revealed that students frequently viewed the forums but contributed relatively few postings, indicating widespread passive participation. Most contributions were concentrated at the triggering and exploration phases, with only about 15% reaching integration or resolution. Interaction maps confirmed a strongly tutor-centered pattern, with minimal peer-to-peer exchanges, while comparison of participation and assignment data showed that more active contributors achieved higher performance. These findings underscore the limited depth of engagement in asynchronous forums but also highlight their potential to support learning when students participate meaningfully. The novelty of this study lies in its triangulated methodology and its focus on physics education in an open and distance learning context. The study contributes empirical evidence for improving asynchronous forum design and facilitation to foster higher-order engagement in physics learning.